WATER HAMMER CAUSED BY SHUT-OFF VALVES IN HYDROPOWER PLANTS - Karadžić, Uroš; Bergant , Anton; Vukoslavčević, Petar; Sijamhodžić, Esad; Fabijan , Drago (Journal of Energy Technology, 2024)
This paper investigates water hammer effects caused by the closure of shut-off valves against discharge. Shut-off valves (turbine inlet valves) in hydropower plants (HPP) can be either of spherical or butterfly type. These valves are traditionally used as safety elements in the system and are closed against discharge only in emergency cases such as turbine runaway and pipeline bursts. Usually, the closure of shut-off valves is controlled by the valve actuator (hydraulic servomotor). Because the hydraulic torque that acts on the valve body is dependent on flow conditions, the valve closing time may vary significantly for different flow velocities. The closure of the shut-off valve can be modelled as passive or active. The passive valve model takes into consideration the dynamic equation of the valve body motion, and the valve closure time is a result of numerical simulation. In the active valve model, the closure time is known in advance. The results of measurements and corresponding numerical simulations for the closure of a butterfly valve from the Lomščica HPP, Slovenia and the closure of a spherical valve from the Perudica HPP, Montenegro are presented. The results for both valves are given for closure against the discharge from maximum (full-load) and half of the maximum discharge (half-load). It is shown that for the case of butterfly valve, the closing time varies significantly with respect to flow conditions. In contrast, the spherical valve closing time is practically the same regardless of hydraulic loads.